2010
DOI: 10.1038/nchembio.289
|View full text |Cite|
|
Sign up to set email alerts
|

Chemical decay of an antibiotic inverts selection for resistance

Abstract: Antibiotics are often unstable, decaying into various compounds with potential biological activities. We found that as tetracycline degrades, the competitive advantage conferred to bacteria by resistance not only diminishes, but reverses to become a prolonged disadvantage due to the activities of more stable degradation products. Tetracycline decay can lead to net selection against resistance, which may help explain the puzzling coexistence of sensitive and resistant strains in natural environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 24 publications
1
56
0
Order By: Relevance
“…Previously, we observed that anhydrotetracycline, a key biosynthetic precursor 41 and degradation product 42 of tetracycline with poor antibiotic activity was not degraded by Tet(47-56) 28 . None the less, it is known to be an effector of tetracycline producers and tetracycline-resistant bacteria by inducing expression of energetically expensive tetracycline efflux pumps, permitting tetracycline producers to survive and selecting against tetracycline resistance 43 . Based on the structural similarity to tetracycline and the intimate role that anhydrotetracycline plays in tetracycline biology, we hypothesized that anhydrotetracycline represents an evolutionarily-privileged chemical lead for inhibitor design.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we observed that anhydrotetracycline, a key biosynthetic precursor 41 and degradation product 42 of tetracycline with poor antibiotic activity was not degraded by Tet(47-56) 28 . None the less, it is known to be an effector of tetracycline producers and tetracycline-resistant bacteria by inducing expression of energetically expensive tetracycline efflux pumps, permitting tetracycline producers to survive and selecting against tetracycline resistance 43 . Based on the structural similarity to tetracycline and the intimate role that anhydrotetracycline plays in tetracycline biology, we hypothesized that anhydrotetracycline represents an evolutionarily-privileged chemical lead for inhibitor design.…”
Section: Resultsmentioning
confidence: 99%
“…Transfer of this self-immunity pump to nonproducer organisms enables them to resist tetracycline [32]. Interestingly, the natural decay of tetracycline to anhydrotetracycline can invert the selective advantage of cohabiting resistant strains over susceptible ones, because of the fitness cost of constitutive TetA expression in the resistant strains through anhydrotetracycline induction [33]. This highlights the complex ecological interplay between antibiotic production, degradation, and resistance.…”
Section: Repurposing Environmental Genes: the 'Original' Resistomementioning
confidence: 97%
“…In this study, transformed E. coli exhibited enhanced susceptibility to aloin than non-transformed E. coli. The increased susceptibility could be explained by 'negative cross-resistance' or 'collateral sensitivity', where the induction of resistance to one compound enhances the toxicity to other compounds (Li et al 2002;Palmer et al 2010). Previously, similar phenomenon was observed through the increased susceptibility of E. coli to fusaric acid consequent to development of resistance against tetracyclines by modification of efflux pumps (Bochner et al 1980).…”
Section: Minimum Inhibitory Concentrationmentioning
confidence: 82%